Principles of clinical and economic analysis of antimicrobial drugs - Y. M. Gomon; A. S. Kolbin; S. O. Mazurenko; I. G. Ivanov (Качественная клиническая практика, 2019)
In light of rising costs in the health care system and the introduction of innovative but expensive technologies, decision makers are looking for reliable methods to assess their cost-effectiveness. To this end, a comprehensive assessment of medical technology is carried out, including the analysis of information on its comparative clinical efficacy and safety, as well as an assessment of the economic consequences of its implementation. One of the most important features of clinical and economic studies of antimicrobials is the ability of infectious agents to acquire resistance to therapy, which fundamentally changes their effectiveness, and, consequently, the clinical and economic feasibility of use over time. Taking into account the risks of resistance as a criterion of effectiveness in pharmacoeconomical studies of antimicrobial drugs is an important factor affecting the feasibility of inclusion of drugs in the restrictive lists. At the same time, this criterion remains underutilized.